(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2025)
This article explores the impact of the green economy on small businesses, focusing on the opportunities and challenges it presents. The transition to a green economy has become a global priority, encouraging businesses to adopt sustainable practices and environmentally friendly technologies. For small businesses, this shift offers prospects for innovation, cost savings, and enhanced market competitiveness. However, it also introduces challenges such as the need for initial investments, compliance with new regulations, and access to green financing. By analyzing case studies and current trends, the article highlights strategies for small businesses to thrive in a green economy while contributing to sustainable development goals. The findings underscore the significance of policy support, capacity building, and stakeholder collaboration in enabling small enterprises to leverage green economic initiatives effectively.